Endothelin-1 Production by Normal Human Cultured Keratinocytes and its Regulation - Hajime Inoue; Nagaoki Wakisaka; Nobuhiro Tane; Kazumasa Ando; Emiko Isono; Miwa Yamanaka; Masaki Aihara; Hirotomo Ishida (Mediators of Inflammation)
The possibility that cultured keratinocytes produce endothelins were investigated. The results showed that cultured keratinocytes derived from normal human skin produce endothelin-1. Moreover, keratinocyte endothelin-1 production was completely inhibited by the presence of actinomycin D in the medium. As in the case of endothelial cells, recombinant interleukin-1β was capable of promoting endothelin-1 production in keratinocytes, whereas herapin inhibited it. Thrombin also inhibited endothelin-1 production. These results indicate that the mechanism of endothelin-1 production in keratinocytes is slightly different from the mechanism in vascular endothelial cells.